2020
DOI: 10.1186/s12944-020-01242-6
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte to High-Density Lipoprotein Ratio (MHR) as a predictor of mortality and Major Adverse Cardiovascular Events (MACE) among ST Elevation Myocardial Infarction (STEMI) patients undergoing primary percutaneous coronary intervention: a meta-analysis

Abstract: Background: Monocyte to High Density Lipoprotein Ratio (MHR) is a new marker that has been associated with major adverse cardiovascular outcomes among STEMI patients. We sought to strengthen the association between MHR and mortality and major adverse cardiovascular events (MACEs) among STEMI patients who underwent primary percutaneous coronary intervention. Methods: Studies were included if they satisfied the following criteria:1) Observational Studies; 2) Adult patients with ST-elevation Myocardial Infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 26 publications
3
44
0
1
Order By: Relevance
“…[36][37][38] The MHR is a new inflammatory marker that has been used for cardiovascular diseases, tumors and, chronic inflammatory diseases. [39][40][41] Aktas Karabay et al 42 found statistically significant difference in MHR between psoriasis patients and control group. Also they reported positive correlation between the psoriasis area and severity index and MHR.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[36][37][38] The MHR is a new inflammatory marker that has been used for cardiovascular diseases, tumors and, chronic inflammatory diseases. [39][40][41] Aktas Karabay et al 42 found statistically significant difference in MHR between psoriasis patients and control group. Also they reported positive correlation between the psoriasis area and severity index and MHR.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that high monocyte counts and low HDL cholesterol levels may be relevant to inflammation 36‐38 . The MHR is a new inflammatory marker that has been used for cardiovascular diseases, tumors and, chronic inflammatory diseases 39‐41 . Aktas Karabay et al 42 found statistically significant difference in MHR between psoriasis patients and control group.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] High NLR values have been reported to be a marker of subclinical inflammation and were an independent predictor of cardiovascular events and mortality in ST-segment elevated MI (STEMI), 31 significantly correlate with SxS, 32 predict severe atherosclerosis in patients with CAD, 33 and predict mortality in hospitalized patients with the acute coronary syndrome. 34 Similarly, high MLR values could identify vulnerable plaques in stable angina 11 were associated with short-and long-term mortality in STEMI patients 35 as well as with inhospital and long-term major adverse cardiac and cerebrovascular events in STEMI patients 31 and were correlated with the SxS. 36 Likewise, it has been found that a high PLR could predict the severity of CAD 37 was associated with poor prognosis in CAD patients 38 was a predictor of long-term mortality in non-STEMI patients, 39 and could predict high-risk critical lower extremity ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…34 However, another big meta-analysis by Villanueva et al found that MHDLr was only associated with a significantly higher IHM, not LTM, a finding opposite to our results. 35 One possible explanation of the underlying mechanism is that the combination of monocyte and HDL-C may be closely linked to chronicle systemic inflammation, endothelial dysfunction, and oxidative stress. 36 Macrophages, transformed from circulating monocytes, are one of the key cell types for atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 99%